Effect of polyethylene glycol 6000 and storage period on seed quality of cocoa (Theobroma cacao L.) - Astiti Rahayu; Triani Hardiyati; Ponendi Hidayat (Indonesian Coffee and Cocoa Research Institute, 2014)
Increased productivity of cocoa needs high quality of cocoa seeds which are generally provided by certified seed gardens located far from smallholders farm, where seed delivery takes long time and may reduce physiological quality of seeds. One effort to maintain the seed quality is by treatment the seeds with polyethylene glycol6000 (PEG 6000). This study was aimed to study the interaction of PEG 6000 concentration and storage period on cocoa seed quality, and to determine the best concentration of PEG 6000 and storage period to maintain cocoa seed quality. The research was conducted in seed storage room, seed laboratory and green houseof PPPPTK, Cianjur. The experimental design used was a factorial completely randomized design and each combination treatment repeated three times. The first factor was concentration of PEG 6000 of 0%, 20%, 40%, and 60%, and the second factor was the storage period of 3 weeks, 6 weeks, 9 weeks, and 12 weeks. The results showed that concentration of PEG 60% with three weeks storage period was able to minimize the number of moldy seeds. The concentration of PEG 20%, 40%, and 60% were able to prevent seed germination in storage until six weeks. Concentration of PEG 6000 20% was able to maintain moisture content, seed germination, and germination rate.Key words:cocoa seed, storage, recalcitrant, PEG